Functional elements and engineering template-based product development process. Application for the support of stamping tool design - Prieur, Michael (Reihe Informationsmanagement im Engineering Karlsruhe / Hrsg.: Universität Karlsruhe (TH), Institut für Informationsmanagement im Ingenieurwesen (IMI), 2006)
This thesis proposes a product design solution based on functional elements and particularly on one of its sub-categories called engineering templates. The approach supports the development process to reach the common goals of time reduction and quality enhancement by shortening the product development times, enabling continuous information flows and capitalizing on engineering knowledge. An example based on the template of a stamping tool illustrates the influence of templates on process chain shaping and evidences their utility for the concurrent engineering concept.